The impact of the Union of Soviet Socialist Republics (USSR) occupation on Afghanistan politics and economy: an empirical study - Mohammad Fawad Basharpal,; Mohd Fuad Mat Jali, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Afghanistan’s unique geopolitical attributes have made it a centre of rivalry among great powers. The 1979 Soviet military intervention set in a new of war and chaos which in turn brought critical changes within the geo-political environment of Afghanistan. Literature suggests that the Soviet Union ocupation was merely the curtailment of the United States in the region and more so an idealogical thing. This study sought to examine empirically the veracity of this proposition. Empirical data were collected from 88 purposively sampled Afghan respondents a number of whom were then selected for further in-depth interviews. The data were analyzed by using SPSS 16 in terms of descriptive statistics, and the one way ANOVA to investigate the differences of socio-demographic data (education, profession and ethnicity) in order to gain insight into perceived differences of USSR economic investment and politics in Afghanistan. The result showed that significant differences were observed as a result of the USSR economic investment and politics in Afghanistan, especially with respect to socioeconomic variables such as education level, ethnicity and professions. Interestingly, 72.7 per cent of respondents perceived USSR occupation as having been favourable to Afghans’ incomes while the same percentage disagreed that the USSR presence had helped reducing insurgence and terrorism. In conclusion, the USSR occupation of Afghanistan was perceived as having some positive impacts with respect to economic investment and politics. However, when taken together negative impacts abound as many respondents did not agree that the occupation was favourable to the Afghan people.